Revealing the role of serum exosomal novel long non-coding RNA NAMPT-AS as a promising diagnostic/prognostic biomarker in colorectal cancer patients - Rizk, Nehal I.; Kassem, Dina H.; Abulsoud, Ahmed I.; AbdelHalim, Sherif; Yasser, Montaser Bellah; Kamal, Mohamed M.; Hamdy, Nadia M. (Life sciences (1973), 2024)
Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide. Nicotinamide phosphoribosyl-transferase (NAMPT) was found to be over-expressed in several cancers including CRC. NAMPT-Antisense (NAMPT-AS) is a novel long non-coding RNA (lncRNA) recently reported to be associated with triple negative breast cancer. However, its role in CRC has not been investigated. This study was designed to explore the role of lncRNA NAMPT-AS in CRC, and to investigate its circulating serum exosomal levels in subjects with/without CRC. We analyzed CRC patients' data in The Cancer Genome Atlas (TCGA). LncRNA NAMPT-AS and NAMPT mRNA levels were measured in serum exosomes isolated from CRC patients and healthy control subjects and were also measured in CRC-tissues using qRT-PCR. Serum NAMPT protein levels were measured by ELISA, and immunohistochemical analyses were done for NAMPT and Ki67 in CRC tissues. Serum exosomal NAMPT-AS levels were found to be significantly higher in CRC patients compared to control subjects and significantly positively correlated with serum exosomal NAMPT mRNA and circulating NAMPT protein. Tissue NAMPT-AS was found to be significantly positively associated with tissue and serum exosomal NAMPT levels. Higher serum exosomal NAMPT-AS levels were found to be associated with higher susceptibility for CRC. Gene-ontology results and survival analysis of TCGA-data showed a potential classification of CRC samples based on NAMPT-AS levels and association of NAMPT-AS upregulation with poor CRC prognosis and survival. These results portray NAMPT-AS as a novel potential diagnostic/prognostic biomarker and key molecular mediator in CRC. [Display omitted] •Serum exosomal lncRNA NAMPT-AS is elevated in CRC patients as compared to controls.•Serum exosomal NAMPT-AS is correlated with exosomal mRNA NAMPT and its serum protein.•High serum exosomal NAMPT-AS is linked to high CRC susceptibility.•CRC tumor TCGA samples can be classified based on NAMPT-AS levels.•NAMPT-AS upregulation is associated with poor CRC prognosis.